PENGARUH DUE PROFESSIONAL CARE, TIME BUDGET PRESSURE, KOMPETENSI, MOTIVASI TERHADAP KUALITAS AUDIT - Amalina, Zata Isma Rizki; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The research studies the influence of Due Professional Care, Time Budget Pressure, Competency and Auditor Motivation to the audit quality. The scope of this research is all auditors who work at Public Accountant Office in Surabaya. The purpose of this research is to analyze the influence of Due Professional Care, Time Budget Pressure, Competency and Auditor Motivation to the audit quality. Based on the characteristic of the problem, this research is a correlation research. This research applies hypothesis and research design in the form of survey, and the samples are 10 Public Accountant Offices in Surabaya and the data is the questionnaires which have issued in Public Accountant Offices. This research has been done by using multiple linear regressions analysis model. The result of the analysis shows that variables i.e. Due Professional Care, Time Budget Pressure, Competency and Auditor Motivation have positive influence to the audit quality. The interpretation is when the Due Professional Care, Time Budget Pressure, Competency and Auditor Motivation that are owned by an auditor is getting high, the audit quality that will be generates is getting better as well.Keywords: Due Professional Care, Time Budget Pressure, Competency and Auditor Motivation, and Audit Quality